(untitled) (The Review of Diabetic Studies, 2025)
Persistent apical periodontitis sticks around in roughly 10-20% of teeth even after solid root canal work, posing a real challenge in dental practice. This review gathered fresh data through October 2025 from key sources like PubMed, Scopus, and more, analyzing 47 studies—32 randomized trials plus 15 cohort follow-ups—tracking over 4,200 teeth for a minimum of one year. Success rates impressed: 91.5% healing with microsurgery using bioceramic retrofills, 87.2% via intentional replantation, and 93.4% through regenerative approaches in young teeth. Bigger lesions above 5 mm, full-thickness bone loss, and poor crown seals dragged results down. Today’s microsurgery with sharp magnification, ultrasonic preps, advanced sealers, and cone-beam guidance beat traditional apicoectomy hands down, boosting outcomes by about 40%. Issues stayed rare under 4%, and over 96% of teeth remained in service past five years. In short, when retreatment without surgery flops or isn’t feasible, modern endodontic microsurgery stands as the top choice for predictable, lasting recovery.